Where giant earthquakes may come. Issue 10 (18th October 2016) - Marzocchi, W.; Sandri, L.; Heuret, A.; Funiciello, F.
Abstract: Giant earthquakes ( M w ≥8.5) usually occur on the boundary between subducting and overriding plates of converging margins, but it is not yet clear which (if any) subduction zones are more prone to produce such a kind of events. Here we show that subduction zones may have different capabilities to produce giant earthquakes. We analyze the frequency‐magnitude distribution of the interplate earthquakes at subduction zones that occurred during 1976–2007 and calculate the propensity (defined as the average annual rate) of giant events for about half of the subduction zones. We find that the b value of interplate earthquakes is significantly different among the subduction zones, and out‐of‐sample giant earthquakes (before 1976 and after 2007) have occurred preferentially in high‐propensity areas. Besides the importance for seismic hazard assessment and risk mitigation, our results seem to indicate that a higher seismicity rate does not necessarily imply a higher likelihood to generate giant earthquakes, and the way in which the stress is released at a subduction interface does not change significantly after the occurrence of such events. Key Points: Subduction zones may have a different capability to produce giant earthquakes The propensity to generate giant earthquakes is not proportional to the interplate seismicity rate Frictional properties of subduction zones are stable through time